Additive manufacturing of multiple materials by selective laser melting : Ti-alloy to stainless steel via a Cu-alloy interlayer - Tey, Cher Fu (2020)
The ability to combine multiple materials (MM) into a single component to expand its range of functional properties is of tremendous value to the ceaseless optimization of engineering systems. Although fusion and solid-state joining techniques have been typically used to join dissimilar metals, additive manufacturing (AM) has the potential to produce MM parts with a complex spatial distribution of materials and properties that is otherwise unachievable. In this work, the selective laser melting (SLM) process was used to manufacture MM parts which feature steep material transitions from 316L stainless steel (SS) to Ti-6Al-4V (TiA) through an interlayer of HOVADUR® K220 copper–alloy (CuA). The microstructure in both the CuA/SS and TiA/CuA interfaces were examined in detail and the latter was found to be the critical interface as it contained three detrimental phases (i.e. L21 ordered phase, amorphous phase, and Ti2Cu) which limit the mechanical strength of the overall MM part. By making use of the non-homogeneity within the melt pool and limiting the laser energy input, the relatively tougher interfacial α′-Ti phase can be increased at the expense of other brittle phases, forming what is essentially a composite structure at the TiA/CuA interface. During tensile testing, the interfacial α′-Ti phase is capable of deflecting cracks from the relatively brittle TiA/CuA interface towards the ductile CuA interlayer and an overall tensile strength in excess of 500 MPa can be obtained. This method of introducing an interfacial composite structure to improve MM bonding is envisioned to be applicable for the SLM of other metallic combinations as well.